2017
DOI: 10.1103/physrevb.95.064103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of loading control on strain bursts and dislocation avalanches at the nanometer and micrometer scale

Abstract: Through three-dimensional discrete dislocation dynamics simulations, we show that by tuning the mode of external loading, the collective dynamics of dislocations undergo a transition from driven avalanches under stress control to quasi-periodic oscillations under strain control. We directly correlate measured intermittent plastic events with internal dislocation activities and collective dynamics. Under different loading modes, the role of the weakest dislocation source and the defect population trend are sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…Strain bursts were found to be dominated by the intermittent operation of the weakest sources [41,43]. However, power law statistics were found to be the result from correlated activation of dislocation sources, and that such correlations are strongly influenced by the loading mode [35,197].…”
Section: Results Of 3d-ddd Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain bursts were found to be dominated by the intermittent operation of the weakest sources [41,43]. However, power law statistics were found to be the result from correlated activation of dislocation sources, and that such correlations are strongly influenced by the loading mode [35,197].…”
Section: Results Of 3d-ddd Simulationsmentioning
confidence: 99%
“…For 1 ∼ 20 µm LiF crystals, a larger power law exponent of 1.8 ∼ 2.9 is found [34]. A detailed summary of the recorded burst quantity and the power law exponent in micro/nano pillars is given in Table 3 of reference [35], and in [23]. It is generally believed that dislocation avalanches result from the collective and correlated dynamics of dislocations [36,37].…”
Section: Micropillarsmentioning
confidence: 99%
“…Instead of mean-field theory arguing for a universal landscape of intermittent plasticity [25], it has been revealed that the associated statistical properties are material-and size-dependent, with varying scaling exponent and wildness [17,32,77]. Note that the loading method in these experiments remain the same, and the varying should not be an effect of machine stiffness analyzed in [78]. On the other hand, we found that the relationship between these two variables, ( ), in pure Al and nano-sized disorder reinforced Al alloys, is "universal" (material-independent) [17].…”
Section: The Universal Relation ( )mentioning
confidence: 98%
“…Plastic deformation of pillars has been extensively studied using experimental (Brinckmann et al, 2008) and modeling (Weinberger and Cai, 2008) approaches, with a focus on the yield/flow stress as a function of the pillar diameter, height-to-diameter aspect ratio, cross-sectional shape, strain rate, temperature, lattice orientations, boundary conditions, etc., in a wide range of metallic materials. For example, the discrete dislocation dynamics (DDD) method, which assumes the motion of dislocations as the only carrier of plasticity, has been applied to simulating nanopillars (Papanikolaou et al, 2017), submicropillars (Cui et al, 2017), and micropillars (El-Awady, 2015). However, besides dislocation slip, processes such as twinning and phase transformation have also been identified as possible plastic deformation mechanisms in nano-/micropillars (Greer and De Hosson, 2011) in both face-centered cubic (FCC) and body-centered cubic (BCC) metallic systems.…”
Section: Introductionmentioning
confidence: 99%